Kinetics of Uropathogenic Escherichia coli Metapopulation Movement during Urinary Tract Infection - Matthew S. Walters (American Society for Microbiology, 2012)
ABSTRACT The urinary tract is one of the most frequent sites of bacterial infection in humans. Uropathogenic Escherichia coli (UPEC) strains are the leading cause of urinary tract infections (UTIs) and are responsible for greater than 80% of uncomplicated cases in adults. Infection of the urinary tract occurs in an ascending manner, with colonization of the bladder leading to possible kidney infection and bacteremia. The goal of this study was to examine the population dynamics of UPEC in vivo using a murine model of ascending UTI. To track individual UPEC lineages within a host, we constructed 10 isogenic clones of UPEC strain CFT073 by inserting unique signature tag sequences between the pstS and glmS genes at the attTn7 chromosomal site. Mice were transurethrally inoculated with a mixture containing equal numbers of unique clones. After 4 and 48 h, the tags present in the bladders, kidneys, and spleens of infected mice were enumerated using tag-specific primers and quantitative real-time PCR. The results indicated that kidney infection and bacteremia associated with UTI are most likely the result of multiple rounds of ascension and dissemination from motile UPEC subpopulations, with a distinct bottleneck existing between the kidney and bloodstream. The abundance of tagged lineages became more variable as infection progressed, especially after bacterial ascension to the upper urinary tract. Analysis of the population kinetics of UPEC during UTI revealed metapopulation dynamics, with lineages that constantly increased and decreased in abundance as they migrated from one organ to another. IMPORTANCE Urinary tract infections are some of the most common infections affecting humans, and Escherichia coli is the primary cause in most uncomplicated cases. These infections occur in an ascending manner, with bacteria traveling from the bladder to the kidneys and potentially the bloodstream. Little is known about the spatiotemporal population dynamics of uropathogenic E. coli within a host. Here we describe a novel approach for tracking lineages of isogenic tagged E. coli strains within a murine host by the use of quantitative real-time PCR. Understanding the in vivo population dynamics and the factors that shape the bacterial population may prove to be of significant value in the development of novel vaccines and drug therapies.